On being required to offer acts of prayer and worship to God - Taylor, Michael Joseph (2005)
The Christian Church, speaking both to its members and to all humankind, proposes, commonly, that human beings are required to offer acts of prayer and worship to God. However much Christian theologians approach the place of prayer and worship in the life of human beings it is not evident that they commonly question the notion that human beings are required to offer prayer and worship to God. In this study I have examined directly, in a manner which is not explicitly and commonly evident within Christian theology, some of the ways in which we might approach the notion that human beings are required to offer acts of prayer and worship to God. The core of this study is an examination of a series of texts drawn from the thirteenth century to the present day which, I show, do offer elements of an answer to my question. I explore the answers I can derive from the Summa Theologiae of Thomas Aquinas, from English and Scottish philosophers and from English devotional writings of the seventeenth and eighteenth centuries, from Kant, from a series of nineteenth and twentieth century philosophers, and from Christian resources of the twentieth and twenty first century. I examine the terms within which the notion of the requirement to offer prayer and worship to God is most commonly set and I explore the ways in which these terms are commonly approached among twentieth century philosophers. Finally, I offer elements of my own approach to the question' Are human beings required to offer acts of prayer and worship to God?'